Linking Image Zones To Database By Using Inverse Voronoi Diagrams: A Novel Liz-Ivd Method - Yüksek, Kemal; Cezayirli, Ahmet (Ieee, 345 E 47Th St, New York, Ny 10017 Usa, 2009)
This study proposes a novel Graphical Method (LIZIVD) as an effective solution to link areas on a raster map to a database containing zone characteristics data. The method involves Inverse Voronoi approach which constructs polygonal mesh structure to define each region individually by using Voronoi points. This approach, when combined with Geographic Information Systems (GIS) particularly using satellite images and/or aerial photography, can be used for land exploration by centrally coordinated mobile robots.